+0  
 
0
811
3
avatar

cos 2x / cos^2(x) * sin^2(x) (integrals) I want to know how to solve it

Guest Jan 18, 2016

Best Answer 

 #2
avatar+19653 
+41

cos 2x / cos^2(x) * sin^2(x) (integrals) I want to know how to solve it

 

\(\small{ \begin{array}{rcll} \frac{ \cos{( 2x )} \cdot \sin^2{(x)} } { \cos^2{(x)} } &=& \frac{ \cos{( 2x )} \cdot [ 1-\cos^2{(x)} ] } { \cos^2{(x)} } \qquad &| \qquad \sin^2{(x)} = 1-\cos^2{(x)} \\ &=& \cos{( 2x )} \cdot \left[ \frac{1-\cos^2{(x)}} {\cos^2{(x)}} \right] \\ &=& \cos{( 2x )} \cdot \left[ \frac{1}{\cos^2{(x)}} -1 \right] \\ &=& \frac{\cos{( 2x )} }{\cos^2{(x)}} -\cos{( 2x )} \qquad &| \qquad \cos{( 2x )} = \cos^2{(x)}- \sin^2{(x)}\\ &=& \frac{ \cos^2{(x)}- \sin^2{(x)} }{\cos^2{(x)}} -\cos{( 2x )} \\ &=& 1- \frac{\sin^2{(x)} }{\cos^2{(x)}} -\cos{( 2x )} \\ &=& 1- \frac{ 1-\cos^2{(x)} }{\cos^2{(x)}} -\cos{( 2x )} \\ &=& 1- \left[ \frac{ 1 } {\cos^2{(x)} }-1 \right] -\cos{( 2x )} \\ &=& 2- \frac{ 1 } {\cos^2{(x)} } -\cos{( 2x )} \\ \end{array} }\)

 

\(\begin{array}{rcll} \int \frac{ \cos{( 2x )} \cdot \sin^2{(x)} } { \cos^2{(x)} } &=& \int 2\ dx -\int \frac{ 1 } {\cos^2{(x)} }\ dx -\int \cos{( 2x )}\ dx \\ \end{array}\)

 

\(\begin{array}{rcll} \text{1.} \qquad \int 2\ dx &=& 2\int dx \\ \int 2\ dx &=& 2x \end{array}\)

 

\(\begin{array}{rcll} \text{2.} \qquad \int \frac{ 1 } {\cos^2{(x)} }\ dx &=& \int \frac{ \sin^2{(x)}+\cos^2{(x)} }{\cos^2{(x)}} \ dx \\ &=& \int (\tan^2{(x)} + 1 )\ dx\\ && \boxed{~ \begin{array}{rcll} \text{we need: } y &=& \tan{(x)} \\ y &=& \frac{\sin{(x)}} {\cos{(x)}} \\ y' &=& \frac{\sin{(x)}} {\cos{(x)}} \left[ \frac{\cos{(x)}} {\sin{(x)}} - \frac{-\sin{(x)}}{\cos{(x)}} \right] \\ y' &=& \tan{(x)} \left[ \cot{(x)} + \tan{(x)} \right] \\ y' &=& 1+ \tan^2{(x)} \\ \end{array} ~}\\ &=& \int (\tan^2{(x)} + 1 )\ dx \\ \text{we substitute:} ~ u &=& \tan{(x)}\\ du &=&\left( 1+\tan^2{(x)} \right)\ dx\\ &=& \int (\tan^2{(x)} + 1 ) \frac{du}{1+\tan^2{(x)}} \\ &=& \int du\\ &=& u\\ \int \frac{ 1 } {\cos^2{(x)} }\ dx &=& \tan{(x)}\\ \end{array}\)

 

\(\begin{array}{rcll} \text{3.} \qquad \int \cos{( 2x )}\ dx \\ \text{we substitute:} ~ u &=& 2x\\ du &=&2\ dx\\ \int \cos{( 2x )}\ dx &=& \int \cos{( u )} \frac{du}{2} \\ &=& \frac12 \cdot \int \cos{( u )} \ du \\ &=& \frac12 \cdot \sin{( u )} \\ &=& \frac12 \cdot \sin{( 2x )} \qquad &| \qquad \sin{( 2x )} = 2\cdot \sin{( 2x )}\cdot \cos{( x )} \\ &=& \frac12 \cdot 2\cdot \sin{( 2x )}\cdot \cos{( x )} \\ \int \cos{( 2x )}\ dx &=& \sin{( x )}\cdot \cos{( x )} \\ \end{array}\)

 

\(\begin{array}{rcll} \int \frac{ \cos{( 2x )} \cdot \sin^2{(x)} } { \cos^2{(x)} } &=& \int 2\ dx -\int \frac{ 1 } {\cos^2{(x)} }\ dx -\int \cos{( 2x )}\ dx \\\\ \int \frac{ \cos{( 2x )} \cdot \sin^2{(x)} } { \cos^2{(x)} } &=& 2x - \tan{(x)}-\sin{( x )}\cdot \cos{( x )} + c \end{array}\)

 

laugh

heureka  Jan 18, 2016
 #1
avatar
+15

Take the integral:
integral cos(2 x) tan^2(x) dx
For the integrand cos(2 x) tan^2(x), substitute u = tan(x) and  du = sec^2(x)  dx:
  =   integral (u^2 cos(2 tan^(-1)(u)))/(u^2+1) du
Write (u^2 cos(2 tan^(-1)(u)))/(u^2+1) as u^2/(u^2+1)^2-u^4/(u^2+1)^2:
  =   integral (u^2/(u^2+1)^2-u^4/(u^2+1)^2) du
Integrate the sum term by term and factor out constants:
  =  - integral u^4/(u^2+1)^2 du+ integral u^2/(u^2+1)^2 du
For the integrand u^4/(u^2+1)^2, do long division:
  =  - integral (-2/(u^2+1)+1/(u^2+1)^2+1) du+ integral u^2/(u^2+1)^2 du
Integrate the sum term by term and factor out constants:
  =  2 integral 1/(u^2+1) du- integral 1/(u^2+1)^2 du- integral 1 du+ integral u^2/(u^2+1)^2 du
The integral of 1/(u^2+1) is tan^(-1)(u):
  =  2 tan^(-1)(u)- integral 1/(u^2+1)^2 du- integral 1 du+ integral u^2/(u^2+1)^2 du
For the integrand 1/(u^2+1)^2, substitute u = tan(s) and  du = sec^2(s)  ds. Then (u^2+1)^2  =  (tan^2(s)+1)^2  =  sec^4(s) and s = tan^(-1)(u):
  =  2 tan^(-1)(u)- integral cos^2(s) ds- integral 1 du+ integral u^2/(u^2+1)^2 du
Write cos^2(s) as 1/2 cos(2 s)+1/2:
  =  2 tan^(-1)(u)- integral (1/2 cos(2 s)+1/2) ds- integral 1 du+ integral u^2/(u^2+1)^2 du
Integrate the sum term by term and factor out constants:
  =  2 tan^(-1)(u)-1/2 integral cos(2 s) ds-1/2 integral 1 ds- integral 1 du+ integral u^2/(u^2+1)^2 du
For the integrand cos(2 s), substitute p = 2 s and  dp = 2  ds:
  =  2 tan^(-1)(u)-1/4 integral cos(p) dp-1/2 integral 1 ds- integral 1 du+ integral u^2/(u^2+1)^2 du
The integral of cos(p) is sin(p):
  =  2 tan^(-1)(u)-(sin(p))/4-1/2 integral 1 ds- integral 1 du+ integral u^2/(u^2+1)^2 du
The integral of 1 is s:
  =  -s/2+2 tan^(-1)(u)-(sin(p))/4- integral 1 du+ integral u^2/(u^2+1)^2 du
The integral of 1 is u:
  =  -s/2-u+2 tan^(-1)(u)-(sin(p))/4+ integral u^2/(u^2+1)^2 du
For the integrand u^2/(u^2+1)^2, use partial fractions:
  =  -s/2-u+2 tan^(-1)(u)-(sin(p))/4+ integral (1/(u^2+1)-1/(u^2+1)^2) du
Integrate the sum term by term and factor out constants:
  =  -s/2-u+2 tan^(-1)(u)-(sin(p))/4+ integral 1/(u^2+1) du- integral 1/(u^2+1)^2 du
The integral of 1/(u^2+1) is tan^(-1)(u):
  =  -s/2-u+3 tan^(-1)(u)-(sin(p))/4- integral 1/(u^2+1)^2 du
For the integrand 1/(u^2+1)^2, substitute u = tan(w) and  du = sec^2(w)  dw. Then (u^2+1)^2  =  (tan^2(w)+1)^2  =  sec^4(w) and w = tan^(-1)(u):
  =  -s/2-u+3 tan^(-1)(u)-(sin(p))/4- integral cos^2(w) dw
Write cos^2(w) as 1/2 cos(2 w)+1/2:
  =  -s/2-u+3 tan^(-1)(u)-(sin(p))/4- integral (1/2 cos(2 w)+1/2) dw
Integrate the sum term by term and factor out constants:
  =  -s/2-u+3 tan^(-1)(u)-(sin(p))/4-1/2 integral cos(2 w) dw-1/2 integral 1 dw
For the integrand cos(2 w), substitute v = 2 w and  dv = 2  dw:
  =  -s/2-u+3 tan^(-1)(u)-(sin(p))/4-1/4 integral cos(v) dv-1/2 integral 1 dw
The integral of cos(v) is sin(v):
  =  -s/2-u+3 tan^(-1)(u)-(sin(p))/4-(sin(v))/4-1/2 integral 1 dw
The integral of 1 is w:
  =  -(sin(p))/4-s/2-u+3 tan^(-1)(u)-(sin(v))/4-w/2+constant
Substitute back for v = 2 w:
  =  -(sin(p))/4-s/2-u+3 tan^(-1)(u)-w/2-1/4 sin(2 w)+constant
Substitute back for w = tan^(-1)(u):
  =  (-1/4 (u^2+1) (sin(p)+2 s+4 u-10 tan^(-1)(u))-u/2)/(u^2+1)+constant
Substitute back for p = 2 s:
  =  (-1/2 (u^2+1) (s+sin(s) cos(s)+2 u-5 tan^(-1)(u))-u/2)/(u^2+1)+constant
Substitute back for s = tan^(-1)(u):
  =  (-1/2 (u^2+1) (2 u-4 tan^(-1)(u)+sin(tan^(-1)(u)) cos(tan^(-1)(u)))-u/2)/(u^2+1)+constant
Simplify using cos(tan^(-1)(z)) = 1/sqrt(z^2+1) and sin(tan^(-1)(z)) = z/sqrt(z^2+1):
  =  (2 (u^2+1) tan^(-1)(u)-u (u^2+2))/(u^2+1)+constant
Substitute back for u = tan(x):
  =  -1/4 sec(x) (5 sin(x)+sin(3 x)-8 cos(x) tan^(-1)(tan(x)))+constant
Which is equivalent for restricted x values to:
Answer: | =  2 x-tan(x)-sin(x) cos(x)+constant

Guest Jan 18, 2016
 #2
avatar+19653 
+41
Best Answer

cos 2x / cos^2(x) * sin^2(x) (integrals) I want to know how to solve it

 

\(\small{ \begin{array}{rcll} \frac{ \cos{( 2x )} \cdot \sin^2{(x)} } { \cos^2{(x)} } &=& \frac{ \cos{( 2x )} \cdot [ 1-\cos^2{(x)} ] } { \cos^2{(x)} } \qquad &| \qquad \sin^2{(x)} = 1-\cos^2{(x)} \\ &=& \cos{( 2x )} \cdot \left[ \frac{1-\cos^2{(x)}} {\cos^2{(x)}} \right] \\ &=& \cos{( 2x )} \cdot \left[ \frac{1}{\cos^2{(x)}} -1 \right] \\ &=& \frac{\cos{( 2x )} }{\cos^2{(x)}} -\cos{( 2x )} \qquad &| \qquad \cos{( 2x )} = \cos^2{(x)}- \sin^2{(x)}\\ &=& \frac{ \cos^2{(x)}- \sin^2{(x)} }{\cos^2{(x)}} -\cos{( 2x )} \\ &=& 1- \frac{\sin^2{(x)} }{\cos^2{(x)}} -\cos{( 2x )} \\ &=& 1- \frac{ 1-\cos^2{(x)} }{\cos^2{(x)}} -\cos{( 2x )} \\ &=& 1- \left[ \frac{ 1 } {\cos^2{(x)} }-1 \right] -\cos{( 2x )} \\ &=& 2- \frac{ 1 } {\cos^2{(x)} } -\cos{( 2x )} \\ \end{array} }\)

 

\(\begin{array}{rcll} \int \frac{ \cos{( 2x )} \cdot \sin^2{(x)} } { \cos^2{(x)} } &=& \int 2\ dx -\int \frac{ 1 } {\cos^2{(x)} }\ dx -\int \cos{( 2x )}\ dx \\ \end{array}\)

 

\(\begin{array}{rcll} \text{1.} \qquad \int 2\ dx &=& 2\int dx \\ \int 2\ dx &=& 2x \end{array}\)

 

\(\begin{array}{rcll} \text{2.} \qquad \int \frac{ 1 } {\cos^2{(x)} }\ dx &=& \int \frac{ \sin^2{(x)}+\cos^2{(x)} }{\cos^2{(x)}} \ dx \\ &=& \int (\tan^2{(x)} + 1 )\ dx\\ && \boxed{~ \begin{array}{rcll} \text{we need: } y &=& \tan{(x)} \\ y &=& \frac{\sin{(x)}} {\cos{(x)}} \\ y' &=& \frac{\sin{(x)}} {\cos{(x)}} \left[ \frac{\cos{(x)}} {\sin{(x)}} - \frac{-\sin{(x)}}{\cos{(x)}} \right] \\ y' &=& \tan{(x)} \left[ \cot{(x)} + \tan{(x)} \right] \\ y' &=& 1+ \tan^2{(x)} \\ \end{array} ~}\\ &=& \int (\tan^2{(x)} + 1 )\ dx \\ \text{we substitute:} ~ u &=& \tan{(x)}\\ du &=&\left( 1+\tan^2{(x)} \right)\ dx\\ &=& \int (\tan^2{(x)} + 1 ) \frac{du}{1+\tan^2{(x)}} \\ &=& \int du\\ &=& u\\ \int \frac{ 1 } {\cos^2{(x)} }\ dx &=& \tan{(x)}\\ \end{array}\)

 

\(\begin{array}{rcll} \text{3.} \qquad \int \cos{( 2x )}\ dx \\ \text{we substitute:} ~ u &=& 2x\\ du &=&2\ dx\\ \int \cos{( 2x )}\ dx &=& \int \cos{( u )} \frac{du}{2} \\ &=& \frac12 \cdot \int \cos{( u )} \ du \\ &=& \frac12 \cdot \sin{( u )} \\ &=& \frac12 \cdot \sin{( 2x )} \qquad &| \qquad \sin{( 2x )} = 2\cdot \sin{( 2x )}\cdot \cos{( x )} \\ &=& \frac12 \cdot 2\cdot \sin{( 2x )}\cdot \cos{( x )} \\ \int \cos{( 2x )}\ dx &=& \sin{( x )}\cdot \cos{( x )} \\ \end{array}\)

 

\(\begin{array}{rcll} \int \frac{ \cos{( 2x )} \cdot \sin^2{(x)} } { \cos^2{(x)} } &=& \int 2\ dx -\int \frac{ 1 } {\cos^2{(x)} }\ dx -\int \cos{( 2x )}\ dx \\\\ \int \frac{ \cos{( 2x )} \cdot \sin^2{(x)} } { \cos^2{(x)} } &=& 2x - \tan{(x)}-\sin{( x )}\cdot \cos{( x )} + c \end{array}\)

 

laugh

heureka  Jan 18, 2016
 #3
avatar+19653 
+10

Sorry:

 

\(\sin{( 2x )} = 2\cdot \sin{( x )}\cdot \cos{( x )}\\ \frac12 \cdot \sin{( 2x )}= \frac12 \cdot2\cdot \sin{( x )}\cdot \cos{( x )}\\ \frac12 \cdot \sin{( 2x )}=\sin{( x )}\cdot \cos{( x )}\\\)

 

laugh

heureka  Jan 20, 2016

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.